Opportunities of job search through social media platforms and its development in Lithuania - Gasparėnienė, Ligita; Matulienė, Snieguolė; Žemaitis, Eigirdas (Business: Theory and Practice, 2021)
3.81 billion or 49.03 percent of people around the world in 2020 have been using social media platforms. On average, everyone has 8.6 accounts on social media platforms. In today’s world, social media platforms control a large part of life, one of which is job search. Job searches through social media platforms are already completing the elimination of older traditional job search methods, and the social network LinkedIn, which has become an interactive resume, is slowly outpacing resumes and cover letters in terms of the ability to share recommendations and various expertise. Employers are increasingly posting open job positions on social media platforms, making job postings simple and easily accessible to all users of social media platforms. The main goal of the presented paper is to introduce the recommendations for developing the process of job search through social media platforms using quantitative analysis. This article highlights the concept and peculiarities of social media platforms, advantaged and disadvantages of job search through SMP. The factors influencing job search through social media platforms were presented and analyzed according to the survey, steps for the further development were presented as well. Recommendation to improve the process of job search were provided after theoretical, methodological and empirical part. The results of the research will help to define the main advantages and disadvantages of job search through SMP from general population of Lithuania, also main concerns regarding its usage were determined. It is faster and easier to find the job through SMP, although do not like that it is necessary to keep an eye on their profile page in the social media, so privacy concern was defined as the biggest disadvantage. The article used the following methods: scientific literature review, quantative analysis (survey).